School toilets: queer, disabled bodies and gendered lessons of embodiment. Issue 8 (17th November 2018) - Slater, Jenny; Jones, Charlotte; Procter, Lisa
ABSTRACT: In this paper we argue that school toilets function as one civilising site [Elias, 1978. The Civilising Process . Oxford: Blackwell] in which children learn that disabled and queer bodies are out of place. This paper is the first to offer queer and crip perspectives on school toilets. The small body of existing school toilet literature generally works from a normative position which implicitly perpetuates dominant and oppressive ideals. We draw on data from Around the Toilet, a collaborative research project with queer, trans and disabled people (aroundthetoilet.wordpress.com) to critically interrogate this work. In doing this we consider 'toilet training' as a form of 'civilisation', that teaches lessons around identity, embodiment and ab/normal ways of being in the world. Furthermore, we show that 'toilet training' continues into adulthood, albeit in ways that are less easily identifiable than in the early years. We therefore call for a more critical, inclusive, and transformative approach to school toilet research.